2008
DOI: 10.1111/j.0908-8857.2008.04218.x
|View full text |Cite
|
Sign up to set email alerts
|

Female and male plumage brightness correlate with nesting failure in azure-winged magpies Cyanopica cyanus

Abstract: Animals may assess the quality of other individuals by using information that is contained in elaborate traits. We investigated the degree of sexual dimorphism in structural blue plumage coloration and the potential signal value of these traits in the azure-winged magpie Cyanopica cyanus. We predicted that in this species blue coloration should signal individual quality in both sexes since both females and males invest significantly in caring for offspring. Males have more saturated UV/blue coloration than fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
1
5
0
Order By: Relevance
“…On the other hand, the same directions of change in all three color variables (i.e. UV/blue chroma, hue and brightness) were reported in structurally colored wings of another cavity nesting species, the azure‐winged magpie (Avilés et al 2008).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…On the other hand, the same directions of change in all three color variables (i.e. UV/blue chroma, hue and brightness) were reported in structurally colored wings of another cavity nesting species, the azure‐winged magpie (Avilés et al 2008).…”
Section: Discussionsupporting
confidence: 53%
“…The period of feather growth is often presented as the only time when feather coloration can be altered because the color of feathers is usually described as fixed once feathers keratinize by the end of molt (Gill 2007). Several studies in the last decade, however, have presented evidence that the color of bird feathers can change between molts, irrespective of the mechanisms of color production (Örnborg et al 2002, McGraw and Hill 2004, Figuerola and Senar 2005, Avilés et al 2008). Experimental studies have investigated a variety of agents that may be responsible for changes in the color of grown feathers including accumulation of dirt (Surmacki and Nowakowski 2007), application of uropygial glad secretions (López‐Rull et al 2010), activity of keratinolytic microbes (Shawkey et al 2007) and sunlight‐induced fading (Surmacki 2008).…”
mentioning
confidence: 99%
“…It is important to note that structural color also can change in the time between molts. UV color decreases with time since molt, possibly due to wear and fat deposition (Avilés et al 2008, Roberts et al 2009 Shawkey et al 2007). In a lab setting, inoculated bacteria degrade the exterior cortex of feathers, exposing the spongy layer and increasing feather brightness (Shawkey et al 2007).…”
Section: Consistency Of Structural Plumage Colormentioning
confidence: 99%
“…Since UV reflectance is associated with dominance in juveniles (Tringali and Bowman 2012), I had predicted that the brighter individuals with greater proportions of chroma would gain access to breeding positions over more dull individuals, but contrary to prediction, breeders and helpers had similar measures of brightness, chroma, and hue when separated by sex ( Figure 11). Since UV brightness is correlated with reproductive fitness in other avian species (Hill 1988, Avilés et al 2008, I acknowledge that my measure of fitness, acquisition of breeding space, may not be as accurate as other measures of reproductive fitness, such as total number of fledglings produced. However, since FSJs are a long-lived species and lifetime reproductive fitness is correlated with age at first breeding (Woolfenden and Fitzpatrick 1984), I feel that acquisition of breeding space was appropriate for the scope of this project and feasible given my research time frame.…”
Section: Effects Of Color On Reproductionmentioning
confidence: 99%
“…Recently, it has been shown that female signalling is positively associated with age and/or experience (Potti, 1993;Cuervo et al, 1996;Tella et al, 1997;Komdeur et al, 2005;Bortolotti et al, 2006;Hegyi et al, 2008b), survival prospects (Hõrak et al, 2001;Roulin & Altwegg, 2007), body size (Amundsen, Forsgren & Hansen, 1997), body condition (Velando, Lessels & Marquez, 2001;Bortolotti et al, 2006), breeding performance and/or immunocompetence (Hanssen, Folstad & Erikstad, 2006;Polo & Veiga, 2006;Potti & Merino, 1996;Morales et al, 2007;Doutrelant et al, 2008), predator avoidance (Avilés, Solís & Valencia, 2008), within-clutch variation in yolk androgens (Gil, Lacroix & Potti, 2006), egg size (Szigeti et al, 2007), offspring quality (Roulin et al, 2000(Roulin et al, , 2001bSiefferman & Hill, 2005), or nestling feeding rate (Jawor et al, 2004), all supporting the idea that female ornamentation may indicate individual quality. In addition, observational and experimental studies have reported assortative mating with respect to individual ornamentation (Roulin, 1999;Griggio et al, 2005;Bortolotti et al, 2006;Hegyi et al, 2007b, but see also Bortolotti et al, 2008) and that more ornamented females are more frequently courted (Torres & Velando, 2005), are selected as primary females in polygynous mating systems (Hegyi et al, 2007a), and obtain more and higher quality sperm from high-quality males during the mating process (Cornwallis & Birkhead, 2007a than less conspicuous females.…”
Section: Introductionmentioning
confidence: 99%